THE NATURE OF THE TEACHER IN THE PERSPECTIVE OF KH. HASYIM ASH'ARI AND IMAM NAWAWI: AN ANALYSIS OF THE BOOK ADABUL ALIM WAL MUTA'ALLIM - Nur Alfiyah; Aminatul Fattachil ‘Izza; Akhmad Nurul Kawakib; Mihmidati Hilmia; Nurhalimah Hasibuan (Jurnal Tatsqif)
Facing the Zillennial generation is one of the challenges for teachers in the digitalization era. In addition, as role models for students, teachers are expected to provide a deep understanding of the limits so that students do not abuse the influence of technology. This study aims to explore the nature of teachers according to KH. Hasyim Asy'ari and Imam Nawawi who are prominent Ulama' figures, with reference to the book Adabul Allim wal Muta'allim by him. The method used is a qualitative approach with a descriptive-analytical design and a type of library research, where data sources are obtained by reading, analyzing and recording various literature materials that are in accordance with the subject matter, then filtered and poured into a theoretical framework. The results of the study reveal that KH. Hasyim Asyari classifies teacher manners or ethics into three aspects, namely; manners towards oneself, students and lessons, while Imam Nawawi into four categories, namely; personal ethics, ethics in learning, ethics in teaching, as well as ethics in examinations and willingness to teach. By doing so, the success of teaching, the blessing of knowledge, and the pleasure of Allah will be obtained. The results of this study can be a reference for strengthening the ethics of the teaching profession in shaping the character of students who are noble and adaptive to the challenges of the digital era.